1969
DOI: 10.1093/chromsci/7.8.515
|View full text |Cite
|
Sign up to set email alerts
|

Separation Efficiency Versus Column Length. An Experimental Study With Capillary Columns

Abstract: The columns of different length used for studying the relation between HETP and column Iength are supposed to exhibit identical characteristics per meter. In the laboratory this condition cannot be rigorously fulfilled. The best approximation probably consists in starting the work with a relatively long capillary column followed by running shorter parts obtained by progressive cutting of the original column. Based on this procedure a marked increase of HETP with increasing column Iength is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…Kwok et a!., ( 12) have shown theoretically that frequently the increase is not linear. This fact was confirmed experimentally by, among others, Halasz (13) and Grob (14) who found that the HETP value of a gas chromatographic column increased with column length. In the experiments done by Grob (14), the increase in HETP was not as rapid as the increase in column length so that the overall plate number increased.…”
Section: Some Factors Influencing the Peak Capacitysupporting
confidence: 58%
See 1 more Smart Citation
“…Kwok et a!., ( 12) have shown theoretically that frequently the increase is not linear. This fact was confirmed experimentally by, among others, Halasz (13) and Grob (14) who found that the HETP value of a gas chromatographic column increased with column length. In the experiments done by Grob (14), the increase in HETP was not as rapid as the increase in column length so that the overall plate number increased.…”
Section: Some Factors Influencing the Peak Capacitysupporting
confidence: 58%
“…This fact was confirmed experimentally by, among others, Halasz (13) and Grob (14) who found that the HETP value of a gas chromatographic column increased with column length. In the experiments done by Grob (14), the increase in HETP was not as rapid as the increase in column length so that the overall plate number increased. Halasz (13, 15) maintains that the aforementioned decrease in efficiency is velocity dependent, becoming worse at a higher flow rate.…”
Section: Some Factors Influencing the Peak Capacitysupporting
confidence: 58%
“…The calculations were based on equivalent w-HETP curves for both long and short columns (S). In a more recent paper, however, Grob and Grob indicated that the efficiency of a capillary column per unit length increases with a decrease in length (9).…”
Section: Versatile Short Capillary Column In Gas Chromatographymentioning
confidence: 95%